2019
DOI: 10.1038/s41598-019-42691-z
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Stress Alters Lifetime Mental Health Trajectories and Cortical Neuromorphology via Epigenetic Regulation

Abstract: Experiences during early development are powerful determinants of lifetime mental health. Here we investigated if ancestral stress regulates the brain’s epigenetic memory to alter neuromorphology and emotionality in the remote F4 progeny. Pregnant female rat dams of the parental F0 generation were exposed to stress on gestational days 12–18. To generate a transgenerational stress lineage, their pregnant daughters (F1), grand-daughters (F2) and great-grand-daughters (F3) remained undisturbed. To generate a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
(118 reference statements)
0
27
0
Order By: Relevance
“…Hence, MPS in males may blunt basal HPA axis activity thus compromising adaptive stress response at particularly vulnerable times in life [93]. Accordingly, we demonstrated previously that MPS upregulates cortical chr gene expression in adult males, but not in females [26]. These findings suggest a characteristic agedependent profile of stress markers to be considered in the prediction and diagnosis of stress-related NCDs.…”
Section: Agingmentioning
confidence: 56%
See 4 more Smart Citations
“…Hence, MPS in males may blunt basal HPA axis activity thus compromising adaptive stress response at particularly vulnerable times in life [93]. Accordingly, we demonstrated previously that MPS upregulates cortical chr gene expression in adult males, but not in females [26]. These findings suggest a characteristic agedependent profile of stress markers to be considered in the prediction and diagnosis of stress-related NCDs.…”
Section: Agingmentioning
confidence: 56%
“…The biological signatures linked to early life adversity are also transmitted across generations. Natural disaster and nutritional birth cohorts [18][19][20][21] as well as experimental studies [3,[22][23][24][25][26][27][28][29] have demonstrated that remote ancestral adverse experiences increase the risk of metabolic, cardiac and renal disease, and mental illness with a sex-specific bias. These adverse health outcomes are linked to epigenetic regulation, including altered microRNA (miRNA) expression [30][31][32].…”
Section: Agingmentioning
confidence: 99%
See 3 more Smart Citations